Penerapan Restorative Justice sebagai Model Perlindungan terhadap Anak (Studi Penanganan Perkara Anak Berhadapan dengan Hukum pada Wilayah Hukum Pengadilan Negeri Dumai Kelas IA) - Ritonga, Muhammad Sacral; Mulyadi, Mahmud; Mustamam, Mustamam (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
The problems in this study, concerning the concept of restorative justice in Law Number 11 of 2012 concerning the Child Criminal Justice System, and regarding the concept of restorative justice as an effort to provide protection for children who are faced with the law, and factors that become obstacles and solutions in implementing restorative justice in the Legal Area of the Class IA District Court of Dumai. This research is empirical juridical research, by conducting research at law enforcement agencies / institutions in the Dumai State IA Class law, concerning the implementation of restorative justice in the Legal Area of the Class IA District Court of Dumai. This research is descriptive analysis, using primary and secondary sources. Data analysis used in this study is qualitative data analysis. Based on the results of the research, the concept of restorative justice in the SPPA Act was implemented through the application of Diversion at every level of the juvenile justice process. Diversion is the transfer of settlement of child cases dealing with the law from the formal process (judicial process) to the formal process, by means of deliberation and consensus which prioritizes restorative justice. The concept of restorative justice will provide protection for ABH, because through the implementation of child diversification it will be kept away from the formal justice process which allows the neglect of children's rights and traumatizes children. The obstacle in the implementation of restorative justice in the legal court area of the IA Dumai class is still a lack of human resources law enforcement officers. Supporting facilities and infrastructures are still very minimal. There is still a lack of socialization to the community.